Sustaining Anti-Hindutva Activism in Aotearoa: Strategies, Challenges and Way Forward - Singh, Sneha (New Zealand Sociology, 2025)
In this paper, I will discuss how Hindutva operates in a small country like Aotearoa New Zealand, through various socio-cultural and religious organizations. The fieldwork for this paper is a part of my larger doctoral research that focuses on anti-Hindutva activism in Aotearoa. The study relies on ethnographic fieldwork and semi-structured interviews to understand the presence of Hindutva and anti-Hindutva activism in the country. I engaged in ethnographic fieldwork and conducted semi-structured with around ten anti-Hindutva activists. Compared to the copious work on Hindutva in the diaspora in other multicultural countries, there is comparatively less literature on the presence of Hindutva in Aotearoa, New Zealand, and even less on the organizations that work to challenge Hindutva in diasporic spaces. In the US and UK context, the progressive literature that challenges Hindutva has focused on sustaining Dalit activism (ACDA, 2009), exposing the organization and scope of Hindutva activities abroad (Sabrang and South Asian Citizen Web, 2002), and protests against welcoming Modi in other countries (Mandavilli and Swamy, 2019), raising awareness and understanding about Hindutva ideology beyond the South Asian diasporic spaces (Narayanan, 2015). Such literature is particularly sparse in the New Zealand context. Dutta (2021) has done some excellent work on the rise of Hindutva in Aotearoa through Hindu cultural and religious organisations; however, it does not focus on the practices of activist organisations in the Indian diasporic communities. As such, this paper will make a valuable and timely contribution by exposing the veiled presence of Hindutva in Aotearoa and then looking at the anti-Hindutva activism that challenges Hindutva in New Zealand. In this paper, I will discuss the methods, challenges, and aspirations of one such organisation called the Aotearoa Alliance of Progressive Indians (AAPI) operating in New Zealand. It has become one of the most prominent organisations (and perhaps the only one in the country) that exclusively focuses on the rise of Hindutva in India and the diaspora.